Nanodelivery vehicles induce remote biochemical changes in vivo. Issue 29 (15th July 2021) - Sikora, Kristen N.; Castellanos-García, Laura J.; Hardie, Joseph M.; Liu, Yuanchang; Farkas, Michelle E.; Rotello, Vincent M.; Vachet, Richard W.
Abstract : Dual-mode mass spectrometry imaging shows that the biochemical effects of anti-TNF-α nanoparticle stabilized capsules occur in regions that are spatially remote from where the nanomaterials accumulate. Abstract : Nanomaterial-based platforms are promising vehicles for the controlled delivery of therapeutics. For these systems to be both efficacious and safe, it is essential to understand where the carriers accumulate and to reveal the site-specific biochemical effects they produce in vivo . Here, a dual-mode mass spectrometry imaging (MSI) method is used to evaluate the distributions and biochemical effects of anti-TNF-α nanoparticle stabilized capsules (NPSCs) in mice. It is found that most of the anticipated biochemical changes occur in sub-organ regions that are separate from where the nanomaterials accumulate. In particular, TNF-α-specific lipid biomarker levels change in immune cell-rich regions of organs, while the NPSCs accumulate in spatially isolated filtration regions. Biochemical changes that are associated with the nanomaterials themselves are also observed, demonstrating the power of matrix-assisted laser desorption/ionization (MALDI) MSI to reveal markers indicating possible off-target effects of the delivery agent. This comprehensive assessment using MSI provides spatial context of nanomaterial distributions and efficacy that cannot be easily achieved with other imaging methods, demonstrating the power of MSI to evaluate both expected and unexpected outcomes associated with complex therapeutic delivery systems.